Proton beam therapy in rectal cancer: A systematic review and meta-analysis. (September 2021) - Fok, Matthew; Toh, Steven; Easow, Jeremy; Fowler, Hayley; Clifford, Rachael; Parsons, Jason; Vimalachandran, Dale
Abstract: Introduction: Locally advanced rectal cancer is often treated with neoadjuvant chemoradiotherapy and surgery. Radiotherapy carries significant risk of toxicity to organs at risk (OAR). Proton beam therapy (PBT) has demonstrated to be effective in other cancers, delivering equivalent dosimetric radiation but with the benefit of improved sparing of OAR. This review compares dosimetric irradiation of OAR and oncological outcomes for PBT versus conventional photon-based radiotherapy in locally advanced rectal cancer. Methods: An electronic literature search was performed for studies with comparative cohorts receiving proton beam therapy and photon-based radiotherapy for rectal cancer. Results: Eight articles with a total of 127 patients met the inclusion criteria. There was significantly less irradiated small bowel with PBT compared to three-dimensional conformal radiation therapy (3DCRT) and intensity-modulated radiation therapy (IMRT) (MD -17.01, CI [-24.06, −9.96], p < 0.00001 and MD -6.96, CI [-12.99, −0.94], p = 0.02, respectively). Similar dosimetric results were observed for bladder and pelvic bone marrow. Three studies reported clinical and oncological results for PBT in recurrent rectal cancer with overall survival reported as 43 %, 68 % and 77.2 %, and one study in primary rectal cancer with 100 % disease free survival. Conclusion: PBT treatment plans revealed significantly less irradiation of OAR for rectal cancer compared to conventional photon-based radiotherapy. Trials for recurrent rectal cancer and PBT have shown promising results. There are currently no ongoing clinical trials for primary rectal cancer and PBT. More research is required to validate its potential role in dose escalation, higher complete response rate and organ preservation without increasing toxicity. Highlights: PBT is being increasingly used worldwide in the treatment of cancer. There are limited trials in rectal cancer and proton beam therapy. PBT offers improved sparing of OAR in rectal cancer compared to x-ray radiotherapy. PBT can potentially reduce the devastating side effects of x-ray radiotherapy. Further research in primary rectal cancer and PBT is desperately needed.